An integrated approach to biomonitoring exposure to styrene and styrene-(7,8)-oxide using a repeated measurements sampling design - Fustinoni, S.; Campo, L.; Manini, P.; Buratti, M.; Waidyanatha, S.; De Palma, G.; Mutti, A.; Foa, V; Colombi, A.; Rappaport, S. M. (Biomarkers, 2008)
Abstract The aim of this work was to investigate urinary analytes and haemoglobin and albumin adducts as biomarkers of exposure to airborne styrene (Sty) and styrene-(7,8)-oxide (StyOX) and to evaluate the influence of smoking habit and genetic polymorphism of metabolic enzymes GSTM1 and GSTT1 on these biomarkers. We obtained three or four air and urine samples from each exposed worker (eight reinforced plastics workers and 13 varnish workers), one air and urine samples from 22 control workers (automobile mechanics) and one blood sample from all subjects. Median levels of exposure to Sty and StyOX, respectively, were 18.2 mg m−3 and 133 µg m−3 for reinforced plastics workers, 3.4 mg m−3 and 12 µg m−3 for varnish workers, and <0.3 mg m−3 and <5 µg m−3 for controls. Urinary levels of styrene, mandelic acid, phenylglyoxylic acid, phenylglycine (PHG), 4-vinylphenol (VP) and mercapturic acids (M1+M2), as well as cysteinyl adducts of serum albumin (but not those of haemoglobin) were significantly associated with exposure status (controls<exposed workers). Also, levels of VP and M1+M2 were significantly affected by smoking, and levels of M1+M2 were significantly affected by GSTM1 polymorphisms. Multiple linear regression analyses of the subject-specific (logged) metabolite levels across exposed workers showed that Sty was a significant predictor for all urinary analytes while StyOX was a significant predictor of PHG only. Interestingly, the log scale regression coefficients for Sty in these models were significantly less than one for all metabolites except M1+M2. This suggests that the natural scale relationships between levels of all Sty metabolites, except M1+M2, displayed downward concavity with increasing Sty exposure, suggestive of saturable metabolism. Levels of the protein adducts were not associated with exposure to either Sty or StyOX among exposed subjects.